Vibration feature of spur gear transmission with non-uniform depth distribution of tooth root crack along tooth width. (November 2021) - Ning, Jieyu; Chen, Zaigang; Wang, Yawen; Li, Yifan; Zhai, Wanming
Highlights: A gear dynamics model considering the non-uniform crack is established by using the 'slice method'. The roll and yaw motions generated by gear slices with uneven crack are considered. Vibration feature of the gear in presence of uneven crack is revealed. The mapping relationship between the vibrations and the severity of crack is established. Abstract: Gear tooth root crack is a typical fault of gear transmissions and it threatens the operation safety of gear systems. Therefore, precise detection of the tooth root crack is of a great significance for the prevention of serious safety accidents. As one of the commonly used methods, vibration-based detection has drawn great attentions. However, the mapping relationship between the vibrations and the severity of tooth root crack has not been established well, especially for the crack with non-uniform distribution due to the complexity of its dynamic modelling. To address this problem, an improved gear dynamics model considering non-uniform distribution of the gear tooth root crack fault is established in this paper by using the 'slice method'. Compared with the traditional methods, the advantage of the proposed model is that it enables the accurate modelling of the non-uniform dynamic mesh forces along tooth width that will further excite the support bearings. Then, the dynamic simulation of the gear transmission with non-uniform tooth root crack is performed. The results indicate that the improved model can reveal the vibration characteristics of the gear transmission due to the extra roll and yaw motions caused by the non-uniform tooth root crack. In addition, the correlation between the vibration and the crack size and location is quantified. This study could provide theoretical reference for quantitative detection and diagnosis of gear tooth root crack.